Doctors - Ready, Dee (Mankato, Minnesota : Capstone Press, 1997)
Explains the clothing, tools, schooling, and work of doctors
Includes bibliographical references and index.
Keywords: Physicians -- Juvenile literature; Medicine -- Juvenile literature